Efeitos de um programa de remediação fonológica nas habilidades de leitura e escrita em alunos com Síndrome de Down - Sás, Roberta Moreno (2009)
Many studies show the importance of remediation programs to improve phonological skills of reading and writing, however few are concerned with results that could be found in students with Down syndrome. Thus, the main objective of the present study was to determine the effectiveness of the program for phonological remediation in the levels of reading and writing in students with the syndrome. The specific objectives were to verify students performance on phonological awareness and abilities on reading and writing. Eight students, with a diagnosis of Down syndrome considered literate by their teachers, participated of the study. They were divided into two groups: experimental group (EG) and control group of expected (CG). The study was conducted in schools where the participants were enrolled and involved three phases: pre-test, intervention and post-test. A design of various groups and tools for selection and characterization of the participants, as well as the measuring the effectiveness of the intervention program, was used. During intervention a Phonological Remediation Program was used and consisted of 8 stages: grapheme-phoneme correspondence 1, Breakdown of phonemes in syllables; Classification pairs words; Breakdown of phonemes in words; graphemephoneme correspondence 2; Identification of phoneme; Segmentation of phoneme and suppression of phoneme. Data analysis were made by comparing the performance of participants in the pre-and post-test. The results demonstrated that the Phonological Remediation Program was effective for students with Down syndrome, since it allowed improvement in the performance in tests of phonological awareness, reading aloud and writing under dictation of by eight students when compared to pre and post test situations. It was concluded that besides being effective, the program is easy to apply and of easy understanding by this population, and provides favorable results in a short period of time. Its application by the teachers of Down syndrome students is important to facilitate reading and writing learning.